The Impacts of Subclinical Varicoceles on Infertile Males - Hammadi, Ibrahim J.; Saeed, Ghassan Th.; Abed Tawney, Read How. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: it is well known that the varicocele affects male fertility and had adverse effects on the findings of the standard seminal analysis. According to size of that veins; the varicoceles are divided into clinical that are discovered in physical examination and their harmful effects are proved and subclinical varicoceles that are only discovered by Doppler examination. And till now, the indication of surgery in cases of subclinical varicocele is still controversial because of poor information about the impact of those non-clinically founded blood vessels on the testicular function.Objective: To assess the seminal fluid, testicular volume, and hormone levels in infertile patients with subclinical varicoceles.Patients and methods: two groups were studied; 79 infertile patients with subclinical varicoceles and 50 healthy males with normal scrotal ultrasound were included as control group. Semen samples were collected from all subjects after at least 48 hours of sexual abstinence in sterile wide containers by masturbation and analyzed for sperm concentration and percentage motility according to WHO criteria (2010). Serum FSH, LH, and Testosterone (T) levels were assessed using Radioimmunoassay. Ultrasound examination was done to evaluate the pampiniform plexus caliber and also measuring the testicular size.Results: LH and Testosterone levels were not statistically different among the two groups. FSH levels were significantly higher in infertile men with subclinical varicoceles than in control group (p